Development of an Integrated Thematic Learning Module Based on Problem Based Learning to Improve Primary School Students' Critical Thinking Abilities - Saniyah Oktarisma; Irdamurni; Risda Amini; Neviyarni (Postgraduate, University of Mataram, 2023)
This research is motivated by the fact that there are still many teachers who teach their students only through thematic textbooks. This research aims to develop an Integrated Thematic learning Module Based on Problem-Based Learning that is valid, practical, and effective in improving the Critical Thinking Ability of Class V Students in Elementary school. The type of research used is Research and Development with the ADDIE development model. Based on the results of the development research carried out, the results obtained were that the validity of the module based on the lesson plan expert obtained an average of 100% (very valid), the material expert validator obtained a result of 91.6% (very valid), the result obtained by the language expert was 76% (valid), and the acquisition of media experts was 69.10% (quite valid). The practicality of the modules carried out by educators and students was carried out as a result of trials carried out on 20 students at SDN 127/II Sungai Arang, and SDN 197/II Pulau Pekan who obtained a total average of 93.83%, and 90.83%. or in the very practical category. The effectiveness of the module developed was carried out by comparing the critical thinking abilities of students who used the module (experimental group) with students who used school textbooks (control group). In the initial stage, both sample groups were given a pretest with the same level of questions. From the results of the analysis, the average for experimental class students was 25.00, and for control class students, the average was 96.90. This research concludes that the development of an integrated thematic learning module based on Problem-Based Learning to improve the critical thinking skills of fifth-grade students in elementary schools is declared valid, practical, and effective